Reference values for the EORTC QLQ-C30 in early and metastatic breast cancer. (January 2020) - Mierzynska, Justyna; Taye, Mekdes; Pe, Madeline; Coens, Corneel; Martinelli, Francesca; Pogoda, Katarzyna; Velikova, Galina; Bjelic-Radisic, Vesna; Cardoso, Fatima; Brain, Etienne; Ignatiadis, Michail; Piccart, Martine; et al.
Abstract: Background: Considering the worldwide incidence of breast cancer (BC) and the importance of health-related quality of life (HRQoL) assessment, there is a growing need to have accurate and up-to-date reference values (RVs). RVs are useful for the design of randomised controlled trials (RCTs) and as benchmarks for comparison of cancer RCTs and health care interventions. This study aimed to provide RVs for the QLQ-C30 in early BC (EBC) and metastatic BC (MBC). General patterns of main results from the EORTC dataset (main dataset) were compared with the PDS dataset (comparison dataset) to see whether they would be consistent across pre-defined covariates. Methods: European Organization for Research and Treatment of Cancer (EORTC) (main dataset) and Project Data Sphere (PDS) (comparison dataset) were searched to identify BC RCTs where baseline HRQoL (before treatment) was assessed with the QLQ-C30. RVs were calculated and stratified by disease stage, age, and when available, performance status (PS), comorbidity and region. RVs were reported using descriptive statistics. Results: Data from three EORTC (n = 4115) and three PDS RCTs (n = 1406) were included in the analysis. While EBC patients presented better HRQoL with high baseline functioning scores and low prevalence of symptoms, MBC patients reported worse HRQoL with lower functioning scores and more prevalence of symptoms. In MBC, poor PS and presence of comorbidities reflected worse baseline HRQoL. No consistent differences were found for age and countries. Conclusion: These up-to-date RVs for the EORTC QLQ-C30 in BC show differences in HRQoL scores between stages, PS, and comorbidities. These findings, supported by an independent dataset, will help the clinical interpretation of scores for BCpatients. Highlights: EORTC QLQ-C30 RVs allow interpretation of HRQOL results in BC. In general, EBC patients reported better HRQOL than MBC patients. A EBC and MBC patients reported low levels of nausea/vomiting. EBC patients reported relatively high levels of physical functioning and insomnia. MBC patients reported relatively high levels of cognitive functioning and fatigue.